EFEKTIVITAS PENYULUHAN PENGETAHUAN MENGENAI SKABIES PADA WALI SANTRI PONDOK PESANTREN DARUS SALAM TORJUN, SAMPANG - Muhammad Za'im Munif; Garuda Nusantara Putra Utomo; Lynda Rossyanti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Increased knowledge about scabies not only needed to be given to students at the schools, but also to the families for minimizing contact with their children whose suffering scabies when they return home. One way to increase knowledge about scabies among the students’ family is to provide them with counseling. The purpose of this study was to evaluate the effectiveness of counseling on scabies to the students’ family of the Pondok Pesantren Darus Salam Torjun, Sampang. This research is a quasi-experimental type with a one group pretest and posttest design which was carried out at Pondok Pesantren Darus Salam Torjun, Sampang on July 11, 2022 to August 1, 2022. 52 participants were obtained using purposive sampling. The research instrument used for this study was a questionnaire containing 15 valid and reliable questions about scabies. The statistical test used was the Wilcoxon test because the pretest and posttest data were not normally distributed. The results of statistical tests showed that there was a difference between the results of the pretest and posttest (p=0.000). The conclusion of this study is that counseling about scabies to the students’ family of the Pondok Pesantren Darus Salam Torjun, Sampang showed effective results.